Learning Strategies at MI Muhammadiyah 03 Weru During the Covid-19 Pandemic - Faiqotin Af’idah; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
The purpose of this study was to determine the strategies applied by MIM Muhammadiyah 3 Weru in learning during the Covid 19 pandemic. This scientific work examines various aspects including: history, strategy, challenges and facilities of MI Muhammadiyah 3 Weru. This research is a descriptive qualitative research. This research data collection technique through interviews, documentation, and observation. Based on the results of research at MI Muhammadiyah 3 Weru, online learning only lasted for a while and then returned to face-to-face learning. The impact arising from the covid 19 pandemic for education has changed the education system and curriculum. The educational curriculum should be streamlined and at the same time less burdensome for students. In addition to negative impacts, there are positive impacts, including 1) Innovation in online learning applications, 2) Teachers become technology literate, 3) Collaboration between teachers and parents, 4) The number of online curses increases at once for free.